2021
DOI: 10.1111/jfpp.15472
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of spray dried curcumin encapsulate prepared using a blend of whey protein, maltodextrin, and gum Arabic

Abstract: In the present work, curcumin encapsulate was prepared by spray drying an emulsion comprising of butteroil as the core material and a mix of whey protein, maltodextrin, and gum Arabic as the wall material. Based upon visual appearance, buffalo milk butteroil was found to be more suitable core material for curcumin as compared to cow milk butteroil. Spray dried encapsulates were packaged in metalized laminated pouches and stored at 25°C and 37°C for 6 months. At the end of the study, about 95% of the core mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Clearly, the adequate selection of the carrier agents in the blend can affect the microencapsulation efficiency of the active ingredient [ 4 ]. For example, Meena et al [ 5 ] microencapsulated curcumin, employing blends of whey protein (WP), MX, and GA. They found that the content of the active ingredient remained at values of 92% and 90% at storage temperatures of 25 and 35 °C, respectively, for a period of 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the adequate selection of the carrier agents in the blend can affect the microencapsulation efficiency of the active ingredient [ 4 ]. For example, Meena et al [ 5 ] microencapsulated curcumin, employing blends of whey protein (WP), MX, and GA. They found that the content of the active ingredient remained at values of 92% and 90% at storage temperatures of 25 and 35 °C, respectively, for a period of 6 months.…”
Section: Introductionmentioning
confidence: 99%